Providing the "Full and Effective Equality" for the Members of National Minorities in Political Life - An Addendum to different Interpretation of International Standards - Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The paper analyzes the whole system of legal norms regulating the electoral matter in order to determine the actual scope of the implementation of international standards " full and effective equality "of members of national minorities in the political life in Serbia. Sufficiency of the measures of positive discrimination in electoral law of the Republic of Serbia is focused on two questions. The first question relates to the regulation of the number of signatures required for the determination and declaration of election lists. The second question relates to the applicability of legal electoral threshold or minimum requirements in terms of the number of votes which must be received for participating in the distribution of seats in case of parties of national minorities. There were very serious differences about these issues in practice and it also had the practical consequences. Legal rules in the election matter only know the exclusion of legal electoral threshold in the final stage of the selection process as a measure of positive discrimination. This is the sufficient measure by which the members of national minorities could be put on an equal position with members of the national majority in the race to win seats.